The Cambridge Handbook of Forensic Psychology / [electronic resource] - Brown, Jennifer M.; Campbell, Elizabeth A. (Cambridge : Cambridge University Press, 2010)
Forensic psychology has developed and extended from an original, narrow focus on presenting evidence to the courts to a wider application across the whole span of civil and criminal justice, which includes dealing with suspects, offenders, victims, witnesses, defendants, litigants and justice professionals. This Handbook provides an encyclopedic-style source regarding the major concerns in forensic psychology. It is an invaluable reference text for practitioners within community, special hospital, secure unit, prison, probation and law enforcement forensic settings, as well as being appropriate for trainees and students in these areas. It will also serve as a companion text for lawyers and psychiatric and law enforcement professionals who wish to be apprised of forensic psychology coverage. Each entry provides a succinct outline of the topic, describes current thinking, identifies relevant consensual or contested aspects and alternative positions. Readers are presented with key issues and directed towards specialized sources for further reference.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Forensic psychology; Forensic Psychiatry